Behavioral Counseling with Self-Management Techniques to Increase Self-Awareness of Educational Staff at Universitas Panji Sakti, Indonesia - Kadek Yati Fitria Dewi; Putu Abda Ursula; Ketut Fethry Utarini (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2025)
This study aims to determine whether behavioral counseling combined with self-management techniques can increase the self-awareness of academic staff at Universitas Panji Sakti. The hypothesis proposed is that if behavioral counseling with self-management techniques is applied effectively, the self-awareness of academic staff will increase. This study uses a Counseling Guidance Action Research (CGAR) approach in two cycles, which consists of the stages of identification, diagnosis, prognosis, counseling, evaluation, and reflection. A purposive sampling technique was used to select 14 academic staff who showed self-awareness and needed improvement based on the initial assessment. The research instruments included questionnaires, interviews, and observations. The validity test was carried out through content validity with an item correlation above 0.70, while the reliability test used Alpha Cronbach with a value of 0.85. The results showed an increase in self-awareness from Cycle I to Cycle II. In Cycle I, 12 out of 14 academic staff increased from 79.8% to 88.6%, with an average increase of 8.8%. The five staff members who did not meet the completion criteria continued to Cycle II, increasing from 80.5% to 88.3% and an average increase of 7.9%. Although two staff members have not reached the